2011
DOI: 10.3892/etm.2011.286
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profiles in patients with prostate carcinoma

Abstract: Abstract. It has been suggested that various cytokines are associated with the pathophysiology of prostate carcinoma (Pca). We profiled ten cytokines (IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, IFN-γ and TNF-α) in the serum levels of 11 patients with organ-confined Pca, 15 with advanced Pca without cachexia, 8 with advanced Pca with cachexia (cachexia group) and 5 healthy males as controls. Cytokines were measured using a highly sensitive fluorescence microsphere system. Compared to the control group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…From this profile, when compared to that of the control group, it appears that serum levels of all cytokines were significantly higher in the cachexia group, and six cytokines (IL-1 β , IL-2, IL-8, IL-12, TNF- α , and IFN- γ ) were significantly higher in the group with advanced Pca without cachexia. However, in the group with organ-confined Pca, only IL-1 β and IL-12 levels were significantly higher compared to the control group [51]. Therefore, the cytokinome profile can be useful to identify new markers of disease progression in presence or absence of other comorbidities.…”
Section: “Cytokinome” and Prostate Cancermentioning
confidence: 99%
“…From this profile, when compared to that of the control group, it appears that serum levels of all cytokines were significantly higher in the cachexia group, and six cytokines (IL-1 β , IL-2, IL-8, IL-12, TNF- α , and IFN- γ ) were significantly higher in the group with advanced Pca without cachexia. However, in the group with organ-confined Pca, only IL-1 β and IL-12 levels were significantly higher compared to the control group [51]. Therefore, the cytokinome profile can be useful to identify new markers of disease progression in presence or absence of other comorbidities.…”
Section: “Cytokinome” and Prostate Cancermentioning
confidence: 99%
“…Epithelial prostate cells (both androgen-dependent and independent) influence the growth and differentiation of both normal cells and cancer cells. It has been shown that the epithelial prostate cells produce pro-inflammatory cytokines 2 , which suggests that cytokines are associated with the pathophysiology of the prostate cancer 3 . In healthy people, immune system components specifically recognize and eliminate tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines produced from tumourous cells and infiltrating immune cells are important factors which enable the survival of tumourous cells and their growth in spite of the existence of tumor specific response. So far, several studies focused on cytokines determined in the blood samples, prostate exprimate and urine of the patients with prostate cancer (CP) 3,7,8,9,10,11 Control group consisted of 20 men with benign prostatic hyperplasia and 15 healthy men (regular physical examination) that had never suffered from active/chronic genito urinary diseaase or any malignant diseases. Tumourous tissue samples for further pathohistological analysis were obtained during the surgical procedure of the CP patients who had undergone the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-1 (IL-1) is an inflammatory cytokine present in tumors that promotes tumor angiogenesis and metastasis [7]. IL-1 is elevated in BCa and PCa tumors [8][9][10][11][12][13] and correlates with low or lost ERα or AR accumulation [10,[14][15][16][17]. We discovered that IL-1 downregulates ERα and AR levels in HR + BCa and PCa cell lines concomitant with the upregulation of pro-survival proteins that are basally high in HR − cell lines [18,19].…”
Section: Introductionmentioning
confidence: 99%